The Effect of Qris Use on Interest and Behavior of Non-Cash Transactions in Indonesia - Forever, Febiwenesya; Joel Imanuel (Jurnal Manajemen dan Keuangan, 2025)
Despite extensive national promotion, the adoption rate of QRIS (Quick Response Code Indonesian Standard) as a digital payment method in Indonesia remains relatively low. This study aims to examine the influence of Perceived Ease of Use (PEU) and Perceived Usefulness (PU) on Consumer Interest (CI) and Consumer Behavior (CB) in utilizing QRIS for non-cash transactions. Using the Technology Acceptance Model (TAM) as the theoretical framework, this research introduces CI as a mediating variable to better understand users’ behavioral responses. A quantitative approach was applied, targeting individuals who have used or are familiar with QRIS. Data were collected from 131 respondents using purposive sampling through an online questionnaire. The data were analyzed using path analysis with the SPSS software. The findings indicate that PEU significantly affects PU, and both PEU and PU positively influence CI. Furthermore, PU and CI have a direct positive impact on CB. Additionally, PU acts as a partial mediator between PEU and CB, as well as between CI and CB. The novelty of this study lies in incorporating CI into the TAM framework to explain QRIS adoption more comprehensively. These findings offer valuable implications for policymakers, financial institutions, and platform developers in formulating strategies that enhance QRIS adoption, thereby supporting the advancement of a cashless economy in Indonesia.